Wildlife and spiritual knowledge at the edge of protected areas: raising another voice in conservation - Bortolamiol, Sarah; Krief, Sabrina; Chapman, Colin A; Kagoro, Wilson; Seguya, Andrew; Cohen, Marianne (Ethnobiology and Conservation, 2018)
International guidelines recommend the integration of local communities within protected areas management as a means to improve conservation efforts. However, local management plans rarely consider communities knowledge about wildlife and their traditions to promote biodiversity conservation. In the Sebitoli area of Kibale National Park, Uganda, the contact of local communities with wildlife has been strictly limited at least since the establishment of the park in 1993. The park has not develop programs, outside of touristic sites, to promote local traditions, knowledge, and beliefs in order to link neighboring community members to nature. To investigate such links, we used a combination of semidirected interviews and participative observations (N= 31) with three communities. While human and wildlife territories are legally disjointed, results show that traditional wildlife and spiritual related knowledge trespasses them and the contact with nature is maintained though practice, culture, and imagination. More than 66% of the people we interviewed have wild animals as totems, and continue to use plants to medicate, cook, or build. Five spirits structure humanwildlife relationships at specific sacred sites. However, this knowledge varies as a function of the location of local communities and the sacred sites. A better integration of local wildlifefriendly knowledge into management plans may revive communities’ connectedness to nature, motivate conservation behaviors, and promote biodiversity conservation.